Pengaruh Pembelajaran PKn Terhadap Kesadaran Menaati Tata Tertib Siswa Kelas Tinggi SDN 166 Laburawung - Ritha Tuken; Shasliani Shasliani; Irma Ati Mega (STKIP Andi Matappa Pangkep, 2023)
This study aims to determine the effect of Civics Learning on Awareness of Obeying School Rules in UPTD SPF High Class students at SDN 166 Laburawung, Soppeng Regency. The approach taken is a quantitative approach to the type of research ex post facto. The type of sampling technique used was purposive sampling with a sample of 42 students. The data collection technique used is a questionnaire or a questionnaire. Data analysis used descriptive data analysis techniques and inferential data analysis techniques. Descriptive statistical results were obtained from the results of scoring and categorization through filling out a questionnaire on student perceptions about Civics learning and an awareness questionnaire on obeying the rules. The results of the analysis using a simple linear regression analysis hypothesis test showed a significant value <0.05 (0.008 <0.05) so that H0 was rejected and H1 was accepted. This it can be concluded that Civics learning has an effect on awareness of obeying school rules for UPTD SPF high school students at SDN 166 Laburawung, Soppeng Regency.